Juz 'Amma Memorization Board Game: An Educational Media to Enhance Students' Interest and Ability in Qur'an Memorization - Layyinah, Rahmatika; Muhtadi, Ali; Asad, Muhammad (Universitas Muhammadiyah Surakarta, 2025)
The memorisation of short Quranic chapters, or Surahs, within elementary religious education frequently poses challenges related to student engagement and rote retention capabilities. Consequently, this study aimed to address these issues through the development and subsequent evaluation of an educational board game, focusing on its feasibility, practicality, and effectiveness. The research employed a Research and Development methodology based on the Borg & Gall model which culminated in a final product trial involving 25 fourth-grade students. Data collection utilised expert validation questionnaires, teacher and student practicality assessments, interest surveys, and both written and oral pre-tests and post-tests. The findings indicated that the board game is highly viable, evidenced by strong ratings from content experts at 91.43% and media experts at 78.05%. Moreover, the product was deemed highly practical by both teachers and students, who awarded it scores of 97.03% and 98.52% respectively. The intervention demonstrated effectiveness through a 16% increase in student interest and enhanced memorisation proficiency, characterised by moderate N-gain scores in written (0.62) and oral (0.43) assessments. The distinct advantage of this board game lies in its integration of five interactive challenge types, specifically memorisation, composition, writing, questioning, and insight, organised within a 14-category chapter system